Beyond the Liberty-Justice Dichotomy: A Constitutional-Maqasid Synthesis for Indonesia's Plural Legal Order - Nurhotia Harahap; Nursaimah Harahap (Lembaga Bale Literasi, 2025)
This article examines the relationship between freedom of enterprise and economic justice in Indonesia’s constitutional order and Islamic economic law, arguing that Indonesian law recognises no unlimited, freestanding right to enterprise: enterprise freedom is constructed through the right to work and dignified livelihood, equality and legal certainty, property protection, economic democracy, environmental sustainability, and state duties toward vulnerable citizens. Islamic economic law contributes a substantive ethical vocabulary—?adl, maslahah, maq??id al-shar??ah, risk-sharing, the prohibition of riba, gharar and maysir, and the redistributive functions of zakat and waqf—whose justice claim depends on institutional performance rather than formal religious labelling. Using a normative-empirical legal method combining conceptual, statutory, case-study, historical, and comparative approaches (Wiratraman, 2019), the study analyses the 1945 Constitution, key statutory instruments, Constitutional Court decisions on electricity and water, and evidence on Islamic social finance, Islamic banking, Aceh’s Sharia economic legislation, and inequality. The findings indicate a conditional constitutional synthesis: enterprise is legitimate when it expands real capabilities and fair opportunity, and regulation is legitimate when lawful, proportionate, accountable, and directed toward public prosperity. The article proposes an integrated framework in which constitutional economic democracy and maq??id-oriented Islamic economic law mutually reinforce inclusive welfare within Indonesia’s plural legal order.